Three-in-One Parenteral Nutrition in Neonates and Pediatric Patients: Risks and Benefits. (June 2015) - Blackmer, Allison Beck; Partipilo, M. Luisa
Parenteral nutrition (PN) is a life-sustaining therapy designed to deliver essential nutrients to patients unable to meet nutrition needs via the enteral route. PN may be delivered via a 2-in-1 system (one solution containing amino acids, dextrose, electrolytes, vitamins, minerals, and fluids and one solution containing intravenous fat emulsions [IVFEs]) or via a 3-in-1 system (all nutrients mixed in one container). Although the use of 3-in-1 PN solutions is not necessarily therapeutically advantageous, certain benefits may exist such as the potential to reduce the risk of contamination due to decreased manipulations; ease of administration, particularly in the home care setting; possible cost savings; and reduced IVFE wastage. However, the incorporation of IVFE in 3-in-1 solutions also presents unique risks for the neonatal and pediatric population such as decreased stability, increased lipid globule size, decreased sterility and the potential for increased microbial growth/infectious complications, the need to use a larger filter size, precipitation and compatibility risks, and an increased chance of catheter occlusion. This review outlines the unique issues and challenges to be considered when formulating neonatal and pediatric 3-in-1 PN admixtures. While 3-in-1 PN solutions may be advantageous for certain pediatric populations, specifically those dependent on home PN, the risks do not outweigh the benefits in neonatal patients, and use should be avoided in this population.